1999
DOI: 10.1186/cc343
|View full text |Cite
|
Sign up to set email alerts
|

Low systemic vascular resistance: differential diagnosis and outcome

Abstract: Objective:To determine the frequency and prognosis of the various causes of low systemic vascular resistance (SVR).Design:Analysis of consecutive patients over a 5-year period; retrospective review.Setting:Medical intensive care unit of a large university hospital.Patients:Fifty-five patients with unexplained hypotension and a SVR less than 800 dynes × s/cm5.Background:There are minimal data in the medical literature determining the frequency or outcome of patients with a low SVR that is unrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Septic shock is the most severe infectious complication in bloodstream infections. Early recognition and successful management of septic shock remain numerous knowledge gaps and challenges, because SAP patients without infections may mimic septic shock [ 30 ]. Patients with septic shock should be timely received antibiotic treatments, because there is a definite guideline to start anti-sepsis shock therapy as early as possible [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Septic shock is the most severe infectious complication in bloodstream infections. Early recognition and successful management of septic shock remain numerous knowledge gaps and challenges, because SAP patients without infections may mimic septic shock [ 30 ]. Patients with septic shock should be timely received antibiotic treatments, because there is a definite guideline to start anti-sepsis shock therapy as early as possible [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Injured endothelial cells result in arginine-vasopressin system dysfunction, which results in increased secretions of tumor necrosis factor, prostacyclin, lipopolysaccharide, reactive oxidants, interleukin-1, circulating endothelin, and nitric oxide, which reduce peripheral vascular resistance and vascular reactivity to vasoconstrictors, causing refractory hypotension [ 18 , 19 ]. Previous adult studies have demonstrated that a low SVRI caused by an impaired endothelium is a predictor of mortality in septic patients [ 20 , 21 ]; however, the clinical application of SVRI has not been well established in children with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used vasoactive-inotropic agents to achieve the target level of 3.3-6.0 L/min/m 2 , and we found that serial SVRI values were significantly lower in the mortality group compared with the survival group. In addition, in the mortality group, despite a gradual increase in SVRI, the prolonged duration of low SVRI meant a longer period of tissue hypoperfusion, indicating more organ damage [ 20 ]. Therefore, lower serial SVRI values can be used as an earlier marker of disease severity and insufficient resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Injured endothelial cells indicate dysfunction of the arginine-vasopressin system, which may increase the secretion of tumor necrosis factor, lipopolysaccharides, interleukin-1, circulating endothelin, and nitric oxide, and decrease systemic vascular resistance, causing vascular hyporesponsiveness to vasoactive agents, thereby resulting in refractory hypotension [19]. Previous reports have shown that lower SVRI is associated with mortality in adults with septic shock [20,21]; however, the clinical utilization of SVRI has not been well surveyed in pediatric septic shock. Our previous study with the same group reported that SVRI was a predictor for in-hospital mortality in pediatric septic shock [22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early higher levels of SVRI may indicate better outcomes. In the mortality group, although the SVRI increased gradually, the prolonged period of a low SVRI indicated a longer duration of tissue hypoperfusion, representing more organ damage [20]. Moreover, lower serial SVRI may allow the early recognition of disease severity and insufficient treatment and prompt the immediate titration of vasoactive-inotropic agents to raise the SVRI.…”
Section: Discussionmentioning
confidence: 99%